Biology of South American fruit fly in blueberry, blackberry, strawberry guava, and Surinam cherry crops - Bisognin, Maicon; Nava, Dori Edson; Lisbôa, Heitor; Bisognin, Alexandre Zandoná; Garcia, Mauro Silveira; Valgas, Ricardo Alexandre; Diez‑Rodríguez, Gabriela Inés; Botton, Marcos; Antunes, Luis Eduardo Corrêa (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to describe the biology of Anastrepha fraterculus in blueberry (Vaccinium ashei), blackberry (Rubus spp.), strawberry guava (Psidium cattleyanum) and Surinam cherry (Eugenia uniflora) fruits. The experiment was carried out in laboratory under controlled conditions of temperature (25±2ºC), relative humidity (70±10%), and photophase (12 hours) to determine insect biological parameters in immature and adult development stages. Anastrepha fraterculus finishes its biological cycle in all studied hosts; however, the Brazilian native fruits (strawberry guava and Surinam cherry) provide better conditions for development of the insect. Biological parameters determined for immature development stadium were similar in the four hosts. Insects reared in Surinam cherry and strawberry guava showed, in the adult phase, longer oviposition period, higher fecundity, and higher female longevity in comparison to insects reared in blueberry and blackberry. Oviposition daily rhythm is longer and more uniform in insects reared in strawberry guava and Surinam cherry fruits, which shows that A. fraterculus is better adapted to native fruits from Southern Brazil.